A method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film
The preparation method of chemically deposition of double-chain quaternary ammonium polymer alloy film of porous polytetrafluoroethylene chemical deposited by plasma surface modification solves the problems of hydrophobicity and water permeability attenuation of PTFE membranes, and significantly improves the antibacterial and filtration performance.
Patent Information
- Application Number
- CN202510067339.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-15
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-01-15
AI Technical Summary
The existing PTFE membranes have problems with strong hydrophobicity and water permeability attenuation, and are facing unsatisfactory antibacterial effects caused by biological contamination.
The preparation method of chemically deposition of double-stranded quaternary ammonium polymer alloy films by chemically deposition of porous polytetrafluoroethylene by plasma surface modification, the membrane is prepared by electrospinning by electrostatically modified by low-temperature plasma activation and double-stranded quaternary ammonium salt chemical modification, and finally heat crosslinking treatment is carried out.
It significantly improves the antibacterial and filtration performance of the membrane. Compared with the inorganic antibacterial powder additive type, the antibacterial efficiency is 50%. It is suitable for use in masks, air conditioners and water treatment filter materials.
Smart Images

Figure CN119455700B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy membrane, belonging to the technical field of functional membranes. Background Art
[0002] With climate change, population growth and the acceleration of globalization, the water crisis is getting worse and the availability of water is decreasing. As people pay more attention to water resources, water treatment technology is becoming more and more mature. At present, membrane technology, iron-carbon micro-electrolysis treatment technology, Fenton and Fenton-like oxidation, ozonation, magnetic separation technology, plasma water treatment technology, etc. have been applied to the purification of organic matter, microorganisms, dyes and heavy metal ions in water bodies. Among them, membrane technology, as one of the most successful and cost-effective technologies, has been widely used in sewage treatment and seawater desalination. Polytetrafluoroethylene (PTFE) is a high-performance polymer material with high thermal stability and good flexibility, mechanical properties and film-forming properties. However, ordinary PTFE membranes have strong hydrophobicity, while commercial PTFE membranes have water permeability attenuation caused by membrane fouling during the filtration process. The existence of these problems hinders the widespread application of ordinary PTFE membranes and commercial PTFE membranes. At the same time, in addition to membrane fouling caused by inorganic deposition and organic attachment, poor adhesion and growth of microorganisms on the membrane is also a common form of membrane fouling, which is called biological fouling. Biological fouling can lead to reduced water permeability, which in turn increases the energy consumption and operating costs of the membrane process. Solving membrane biofouling has become one of the most challenging problems in membrane technology. In current research, a lot of work is focused on improving the membrane's anti-biological fouling performance by adding antimicrobial agents to prepare composite membranes, that is, adding a very small amount of antimicrobial agents such as metal ion types (Ag, Zn, Cu, etc.) and oxide photocatalytic types (such as TiO2, Zn0, etc.) to the membrane to give the resulting membrane a certain degree of antibacterial properties. However, the effects of antibacterial properties and inhibition of membrane biofouling are not ideal. Summary of the invention
[0003] In view of this, the present application provides a method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy membrane, which not only gives the membrane a larger specific surface area and improves the plasma activation efficiency, but also significantly improves the antibacterial and filtration properties.
[0004] Specifically, the present application is implemented through the following scheme:
[0005] A method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy membrane, the steps are as follows:
[0006] Step 1: polyvinyl alcohol (PVA) is dissolved in water to obtain a PVA aqueous solution, and then zinc chloride (white solid powder, purity> 98%) is added to obtain a zinc chloride PVA solution.
[0007] PVA preferably has a low to medium molecular weight and a moderate alcoholysis degree. The molecular weight of the PVA is 5000 to 50000, and the alcoholysis degree is 80 to 100%.
[0008] The mass concentration of the PVA aqueous solution is 1-30%,
[0009] The amount of zinc chloride added is 0.5~5% of the mass of PVA.
[0010] In this process, PVA is added with water and stirred for 10 to 30 minutes. After being evenly dissolved, zinc chloride is added and stirred for 15 to 30 minutes to obtain a zinc chloride PVA solution. The stirring speed is 100 to 300 r / min.
[0011] Step 2: Add PTFE to the zinc chloride PVA solution and stir evenly. The amount of PTFE added is 100-900% of the mass of PVA.
[0012] In this process, PTFE powder is added to the zinc chloride PVA aqueous solution, and stirred at high speed for 20 to 60 minutes at a stirring speed of 600 to 1000 r / min to finally form a uniform emulsion state.
[0013] Step three, dissolving the solution obtained in step two in an organic solvent to prepare a spinning solution, and electrospinning the spinning solution to obtain a porous polytetrafluoroethylene membrane. The spinning solution concentration is 5-30%, the spinning voltage of the electrospinning is 10-100KV, the spinning distance is 10-40cm, and the propulsion speed is 0.06-6mm / min.
[0014] Step 4: subjecting the porous polytetrafluoroethylene membrane to low-temperature plasma surface activation treatment, and then chemically surface modifying it with a double-chain quaternary ammonium salt, drying it, and thermally cross-linking it to obtain a finished product.
[0015] Further, as a preference:
[0016] In step one,
[0017] The molecular weight of the PVA is 20000-40000, and the alcoholysis degree is 80-90%. The molecular weight of the PVA is 30000-40000, and the alcoholysis degree is 85-90%, and the molecular weight of the PVA is 30000 and the alcoholysis degree is 88%, which is the best.
[0018] The mass concentration of the PVA aqueous solution is 1-2.4%, and the amount of zinc chloride added is 0.5-2% of the mass of PVA. The best mass concentration of the PVA aqueous solution is 1.8%, and the amount of zinc chloride added is 1.5% of the mass of PVA.
[0019] In step 2,
[0020] The amount of PTFE added is 400~900% of the mass of PVA, and the best amount of PTFE added is 733% of the mass of PVA.
[0021] In step three,
[0022] The spinning solution concentration is 5-20%, the spinning distance is 10-25 cm, and the propulsion speed is 0.06-0.84 mm / min. The best spinning solution concentration is 15%, the spinning distance is 25 cm, and the propulsion speed is 0.72 mm / min.
[0023] The organic solvent is any one of ethanol, acetone and dimethylformamide (DMF), and the concentration of the spinning solution is changed by controlling the amount of the organic solvent added.
[0024] In step four,
[0025] The processing power of low temperature plasma surface activation treatment is 5~20MHz, the processing time is 10~60min, and the processing temperature is 20-30℃. It is best to process at 5~15MHz for 10~20min.
[0026] The film is chemically surface modified by a double-chain quaternary ammonium salt by surface coating deposition, wherein the coating amount of the double-chain quaternary ammonium salt is 0.1-2% of the mass of the porous polytetrafluoroethylene membrane. More preferably, the coating amount is 0.1-1% of the mass of the porous polytetrafluoroethylene membrane. The coating amount is preferably 0.8% of the mass of the porous polytetrafluoroethylene membrane.
[0027] The double-chain quaternary ammonium salt is specifically didecyldimethylammonium chloride or didecyldimethylammonium bromide.
[0028] The drying temperature is 60~120℃ and the drying time is 30~120min.
[0029] The thermal crosslinking temperature is 120-240° C., and the thermal crosslinking time is 60-180 min.
[0030] After the thermal crosslinking, water washing is performed at a temperature of 20-50° C. and the number of water washings is 1-5 times to remove the unreacted double-chain quaternary ammonium salt on the surface.
[0031] The invention adopts double-chain quaternary ammonium salt as an organic antibacterial agent, combines the double-chain quaternary ammonium salt with a PTFE film, increases the deposition and chemical reaction performance of the double-chain quaternary ammonium salt on the film surface through a plasma activation technology, and the added PVA component improves the hydrophilicity and plasma activation efficiency of the film, thereby improving the filtration efficiency and antibacterial performance of the film. Compared with the inorganic antibacterial powder added type, the antibacterial efficiency is improved by 50%, and the invention is particularly suitable for the development of masks, air conditioners, and water treatment filter materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0033] Figure 1 The left figure in the figure is a SEM image of the film after drying in step (4) of Example 34. Figure 1 The right picture in the figure is a SEM image of the film after thermal crosslinking in step (5) of Example 34. DETAILED DESCRIPTION
[0034] In order to make the technical problems, technical solutions and beneficial effects to be solved by this application clearer, the technical solutions in the embodiments of this application will be further described in detail below in conjunction with the drawings in the embodiments of this application. It should be understood that the specific embodiments described herein are only used to explain this application and are not used to limit the technical solutions of this application. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0035] Example 1
[0036] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0037] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 5000, alcoholysis degree 80%, PVA added to deionized water and stirred for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min, and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt didecyl dimethyl ammonium chloride.
[0038] The obtained film was observed to have a diameter of 2 microns by SEM; the antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71; the filtration barrier efficiency was tested according to the test standard of GB / T19083-2010, and the test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, and the filtration efficiency was 87%; the contact angle was 58°.
[0039] Since the molecular weight of PVA is too low, it will be lost seriously in the later elution process, thus affecting the pore size of the membrane, so medium molecular weight PVA was selected for testing.
[0040] Example 2
[0041] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0042] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 20000, alcoholysis degree 80%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min, and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt didecyl dimethyl ammonium chloride.
[0043] The obtained film was observed to have a diameter of 2 microns by SEM; the antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71; the filtration barrier efficiency was tested according to the test standard of GB / T19083-2010, and the test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, and the filtration efficiency was 89%; the contact angle was 51°.
[0044] Example 3
[0045] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0046] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 80%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the amount added is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0047] The obtained film was observed to have a diameter of 2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 92% and a contact angle of 49°.
[0048] Example 4
[0049] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0050] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 40000, alcoholysis degree 80%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the amount added is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0051] The obtained film was observed to have a diameter of 2.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 71 / 72 / 70. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 91% and a contact angle of 55°.
[0052] At this time, continuing to increase the molecular weight will reduce the filtration efficiency. This is mainly because the high molecular weight leads to excessive viscosity of the classic spinning solution, which increases the fiber diameter and reduces the filtration efficiency. A contact angle of less than 80° is considered to be hydrophilic, and the smaller the contact angle, the better the hydrophilicity. The smaller the PVA molecular weight, the better the hydrophilicity. However, lower molecular weight is easily dissolved in water and precipitated, and the content in the film is lower. Therefore, based on the above embodiments, it can be seen that the molecular weight of PVA is 20,000~40,000, and the molecular weight of PVA is preferably 30,000~40,000. The best effect is achieved when the PVA molecular weight is 30,000.
[0053] Example 5
[0054] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0055] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 85%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0056] The obtained film was observed to have a diameter of 2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 93% and a contact angle of 48°.
[0057] Example 6
[0058] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0059] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0060] The obtained film was observed to have a diameter of 2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 94% and a contact angle of 46°.
[0061] Example 7
[0062] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0063] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 90%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 400% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0064] The obtained film was observed to have a diameter of 2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 72 / 73 / 71. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 93% and a contact angle of 47°.
[0065] In summary: the alcoholysis degree is preferably 80-90%, and the alcoholysis degree is preferably 85-90%. When the alcoholysis degree of PVA is 88%, it has the best water solubility, so the spinning solution is the most uniform, and the filtration effect is best at this time.
[0066] Example 8
[0067] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0068] (1) Preparation of zinc chloride PVA aqueous solution: prepare 2% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the amount added is 250% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0069] The obtained film was observed to have a diameter of 2.5 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 68 / 70 / 69. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency of 90% and a contact angle of 45°.
[0070] At this time, the ratio of PVA to PTFE was adjusted, and it was found that when the PVA content in the electrospinning solution increased, the fiber became coarser, and the filtration efficiency and antibacterial performance decreased. Therefore, the amount of PTFE added should be controlled at more than 250% of the mass of PVA.
[0071] Example 9
[0072] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0073] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 0.7% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 614% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0074] The obtained film was observed to have a diameter of 1.5 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 75 / 77 / 74. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 95% and a contact angle of 46°.
[0075] Example 10
[0076] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0077] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 0.6% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0078] The obtained film was observed to have a diameter of 1.3 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 78 / 79 / 76. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 96% and a contact angle of 47°.
[0079] Embodiment 11
[0080] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0081] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 0.5% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 900% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 5%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0082] The obtained film was observed to have a diameter of 1.4 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 78 / 79 / 76. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 95% and a contact angle of 50°.
[0083] At this time, if the proportion of PVA in the electrospinning solution continues to decrease, the fiber diameter becomes coarser, and the filtration efficiency and antibacterial properties decrease. Therefore, the PTFE addition amount is appropriately controlled to be 400~900% of the PVA mass. When the PVA to PTFE ratio is 100:733 (that is, the PTFE addition amount is 733% of the PVA mass), it is optimal.
[0084] Example 12
[0085] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0086] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.2% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the amount added is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 10%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0087] The obtained film was observed to have a diameter of 1.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 79 / 81 / 78. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 97% and a contact angle of 43°.
[0088] Example 13
[0089] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0090] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0091] The obtained film was observed to have a diameter of 1.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 81 / 84 / 80. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 98% and a contact angle of 41°.
[0092] Embodiment 14
[0093] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0094] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 2.4% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 0.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 20%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0095] The obtained film was observed to have a diameter of 1.3 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 80 / 82 / 79. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 97% and a contact angle of 42°.
[0096] At this time, if the concentration of the electrospinning solution continues to increase, the antibacterial and filtration efficiencies will decrease. Therefore, the concentration of the spinning solution should be controlled at 5-20%, and the optimal spinning concentration is 15%.
[0097] Embodiment 15
[0098] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0099] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0100] The obtained film was observed to have a diameter of 1.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 82 / 85 / 81. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 98% and a contact angle of 40°.
[0101] Example 16
[0102] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0103] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0104] The obtained film was observed to have a diameter of 1.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 84 / 86 / 82. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 98% and a contact angle of 40°.
[0105] Embodiment 17
[0106] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0107] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 2% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 10cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0108] The obtained film was observed to have a diameter of 1.2 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 83 / 84 / 81. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 96% and a contact angle of 41°.
[0109] Continuing to add zinc chloride at this time will not increase the antibacterial filtration efficiency. On the contrary, the increase in its content will lead to uneven pores, reducing the antibacterial efficiency and the filtration efficiency. Therefore, the amount of zinc chloride added is 0.5~2% of the mass of PVA, and the best amount is 1.5% of the mass of PVA.
[0110] Embodiment 18
[0111] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0112] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 15cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0113] The obtained film was observed to have a diameter of 0.9 microns by SEM. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 86 / 89 / 85. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency of 99% and a contact angle of 35°.
[0114] Embodiment 19
[0115] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0116] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 20cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0117] The obtained film was observed by SEM to have a diameter of 0.5 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 89 / 90 / 87. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency of 99% and a contact angle of 35°.
[0118] Embodiment 20
[0119] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0120] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0121] The obtained film was observed by SEM to have a diameter of 0.3 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 91 / 92 / 89. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 99% and a contact angle of 34°.
[0122] Embodiment 21
[0123] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0124] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 30cm, and the propulsion speed is 0.06mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0125] At this time, since the spinning distance is too long and the film is uneven, sampling cannot be performed for testing. Therefore, the spinning distance should be controlled at 10-25 cm, and the optimal spinning distance is 25 cm.
[0126] Embodiment 22
[0127] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0128] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.12mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0129] The obtained film was observed by SEM to have a diameter of 0.3 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 92 / 93 / 90. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 99% and a contact angle of 34°.
[0130] Embodiment 23
[0131] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0132] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.24mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0133] The obtained film was observed by SEM and had a diameter of 0.3 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 93 / 94 / 91. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 34°.
[0134] Embodiment 24
[0135] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0136] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.48mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0137] The obtained film has a diameter of 0.3 microns as observed by SEM, and its antibacterial effect is tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effect on Escherichia coli, Staphylococcus aureus and white streptococci is 94 / 94 / 92. The filtration barrier efficiency is tested according to the test standard of GB / T19083-2010, and the test sample is prepared into an SMS type mask, wherein M is the electrospun film invented by this technology, and the filtration efficiency is greater than 99%, and the contact angle is 33°.
[0138] Embodiment 25
[0139] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0140] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.60mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0141] The obtained film was observed by SEM to have a diameter of 0.2 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 94 / 94 / 94. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 31°.
[0142] Embodiment 26
[0143] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0144] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0145] The obtained film was observed by SEM to have a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 95 / 96 / 95. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0146] Embodiment 27
[0147] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0148] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.84mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 5 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0149] The obtained film was observed by SEM and had a diameter of 0.2 microns. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 94 / 95 / 93. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 99% and a contact angle of 32°.
[0150] At this time, if the electrospinning solution propulsion speed continues to increase, the fiber diameter becomes thicker, and the antibacterial and filtration efficiency decreases. Therefore, the electrospinning solution propulsion speed should be controlled at 0.06~0.84mm / min, and 0.72mm / min is the best.
[0151] Embodiment 28
[0152] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0153] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 10 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0154] The obtained film was observed by SEM to have a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 96 / 97 / 95. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0155] Embodiment 29
[0156] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0157] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0158] The obtained film was observed by SEM and had a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effect on Escherichia coli, Staphylococcus aureus and white streptococci was 97 / 97 / 96. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0159] Embodiment 30
[0160] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0161] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 20 MHz, a treatment time of 10 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0162] The obtained film was observed by SEM and had a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effect on Escherichia coli, Staphylococcus aureus and white streptococci was 97 / 97 / 96. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0163] At this time, if the plasma treatment power continues to increase, the antibacterial effect will no longer increase, indicating that the plasma surface activation treatment power of 5~15MHz is optimal, and the best effect can be achieved when the treatment power is 15MHz.
[0164] Embodiment 31
[0165] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0166] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 20 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0167] The obtained film was observed by SEM to have a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 97 / 98 / 97. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0168] Embodiment 32
[0169] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0170] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 30 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.5% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0171] The obtained film was observed by SEM to have a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 97 / 98 / 97. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 30°.
[0172] The antibacterial effect no longer increases with increasing plasma treatment time, indicating that a plasma surface activation treatment time of 10 to 20 minutes is more appropriate, and 20 minutes is sufficient.
[0173] Embodiment 33
[0174] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0175] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 20 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.1% of the mass of the film. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0176] The obtained film was observed by SEM and had a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effects on Escherichia coli, Staphylococcus aureus and white streptococci were 77 / 78 / 75. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 35°.
[0177] Embodiment 34
[0178] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0179] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 20 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 0.8% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0180] The obtained film was observed by SEM to have a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effect against Escherichia coli, Staphylococcus aureus and white streptococci was 100 / 100 / 99. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M is the electrospun film invented by the present technology, with a filtration efficiency greater than 99% and a contact angle of 28°.
[0181] Embodiment 35
[0182] The preparation method of a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film in this embodiment is as follows:
[0183] (1) Preparation of zinc chloride PVA aqueous solution: Prepare 1.8% PVA aqueous solution, PVA molecular weight 30000, alcoholysis degree 88%, stir for 20 minutes to dissolve evenly, add zinc chloride and continue stirring for 20 minutes, the amount of zinc chloride added is 1.5% of the mass of PVA, and the stirring speed is 200r / min. (2) Compounding technology of zinc chloride PVA aqueous solution and polytetrafluoroethylene: Add PTFE powder to the uniformly stirred zinc chloride PVA aqueous solution, the addition amount is 733% of the mass of PVA, stir at high speed for 40 minutes, and the stirring speed is 800r / min. (3) Preparation of porous polytetrafluoroethylene film by electrospinning: Prepare porous polytetrafluoroethylene film by electrospinning process, the spinning solution concentration is 15%, the spinning voltage is 60KV, the spinning distance is 25cm, and the propulsion speed is 0.72mm / min. The medium of the spinning solution is the compound of step (2), and the solvent is DMF. (4) The film obtained in step (3) was subjected to low-temperature plasma surface activation treatment at a power of 15 MHz, a treatment time of 20 min and a treatment temperature of 25°C, and then the film was chemically surface modified with didecyl dimethyl ammonium chloride by surface coating deposition, and the coating amount of didecyl dimethyl ammonium chloride was 1.0% of the film mass. After modification, it was dried at 60°C for 90 min. (5) The antibacterial hydrophilic porous polytetrafluoroethylene filter membrane obtained in step (4) was subjected to thermal crosslinking treatment at a thermal crosslinking temperature of 120°C and a thermal crosslinking time of 120 min, and then washed with water (washed with water at 20°C for 3 times) to remove the unreacted double-chain quaternary ammonium salt.
[0184] The obtained film was observed by SEM and had a diameter of 0.1 micron. The antibacterial effect was tested according to the test standard of GB / T 20944.3-2008, and the antibacterial effect against Escherichia coli, Staphylococcus aureus and white streptococci was 100 / 100 / 100. The filtration barrier efficiency was tested according to the test standard of GB / T19083-2010. The test sample was prepared into an SMS type mask, wherein M was the electrospun film invented by the present technology, with a filtration efficiency of 98% and a contact angle of 31°.
[0185] The coating amount of double-chain quaternary ammonium salt is the biggest factor affecting antibacterial properties. However, as the coating amount increases, the porosity of the film will decrease. This is mainly due to the decrease in porosity caused by thermal cross-linking, which in turn reduces the filtration efficiency. The coating amount of double-chain quaternary ammonium salt is preferably 0.1-2% of the mass of the porous polytetrafluoroethylene membrane.
[0186] Combining the antibacterial and filtration performances of the above embodiments, Example 34 is the best preparation process. The films before and after thermal crosslinking were tested by electron microscopy. The results show that after thermal crosslinking treatment, the double-chain quaternary ammonium salt is anchored on the surface of the film by chemical action. At the same time, the PVA in the film will not dissolve and migrate into the water during later use, resulting in a decrease in its hydrophilicity and filtration performance.
[0187] The above-mentioned embodiments only express several feasible implementation methods of the present invention, and the description is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention, and the embodiments are not used to limit the scope of protection in the claims of the present invention. For ordinary technicians in this field, several modifications and improvements can be made without departing from the concept of the present invention, and all equivalent implementations or changes that do not depart from the present invention should be included in the technology of the present invention.
Claims
1. A method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film, characterized in that: Here are the steps: Step 1: PVA is dissolved in water to obtain a PVA aqueous solution, and then zinc chloride is added to obtain a zinc chloride PVA solution. The molecular weight of the PVA is 5000-50000, and the alcoholysis degree is 80-100%. The mass concentration of PVA aqueous solution is 1~30%, The amount of zinc chloride added is 0.5~5% of the mass of PVA; Step 2: Add PTFE to the zinc chloride PVA solution and stir evenly. The amount of PTFE added is 100-900% of the mass of PVA. Step 3, dissolving the solution obtained in step 2 in an organic solvent to obtain a spinning solution, and electrospinning the spinning solution to obtain a porous polytetrafluoroethylene membrane, wherein the concentration of the spinning solution is 5-30%, the spinning voltage of the electrospinning is 10-100 KV, the spinning distance is 10-40 cm, and the propulsion speed is 0.06-6 mm / min; Step 4: After the porous polytetrafluoroethylene membrane is subjected to plasma surface activation treatment, the polytetrafluoroethylene membrane is chemically surface modified with a double-chain quaternary ammonium salt by surface coating deposition, dried, and thermally cross-linked to obtain a finished product, and the coating amount is 0.1-2% of the mass of the porous polytetrafluoroethylene membrane.
2. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The molecular weight of the PVA is 20,000-40,000, and the alcoholysis degree is 80-90%.
3. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The molecular weight of the PVA is 30,000-40,000, and the alcoholysis degree is 88-90%.
4. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The mass concentration of the PVA aqueous solution is 1-2.4%, the amount of zinc chloride added is 0.5-2% of the mass of PVA, and the amount of PTFE added is 400-900% of the mass of PVA.
5. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The spinning solution concentration is 5-20%, the spinning distance is 10-25 cm, and the propulsion speed is 0.06-0.84 mm / min.
6. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The processing power of the plasma surface activation treatment is 5-20 MHz, and the processing time is 10-60 minutes.
7. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The coating amount is 0.1~1% of the mass of the porous polytetrafluoroethylene membrane.
8. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The drying temperature is 60~120℃ and the drying time is 30~120min.
9. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to claim 1, characterized in that: The thermal crosslinking temperature is 120-240° C., and the thermal crosslinking time is 60-180 min.
10. The method for preparing a plasma surface modified porous polytetrafluoroethylene chemically deposited double-chain quaternary ammonium salt polymer alloy film according to any one of claims 1 to 9, characterized in that: After the thermal crosslinking, water washing is performed at a temperature of 20-50° C. and the number of water washings is 1-5 times.
Citation Information
Patent Citations
Antibacterial hydrophilic hollow fiber assembly for water treatment
CN103752174A
Controllable hydrophobic antibacterial fiber membrane and preparation method thereof
CN109837734A